Suicide risk in systemic lupus erythematosus: a narrative review - Barros, Solange Murta; Araújo, Danilo Barral de; Carvalho, Jozélio Freire de (Revista de Ciências Médicas e Biológicas, 2020)
Introduction: the restrictions imposed by the disease and the perception of personal and social losses related to its course, despite the medical and scientific advances, reinforce fear and generate intense suffering in lupus patients. Psychiatric comorbidities, especially major depressive episodes, are highly prevailing during the course of systemic lupus erythematosus. Among them, suicide is a behavior that is much more common then we believe. Objective: to perform a narrative review on suicidal behavior associated with systemic erythematosus lupus (SLE). Results: studies have shown an increased risk of suicide among patients with chronic diseases and psychiatric disorder, especially depression. However, suicide occurrence cannot be attributed only to a higher prevalence of depression and other mental illnesses. It is necessary to learn more about the suicide risk factors that can be present in patients with lupus to work on a secondary prevention, and avoid not only the premature loss of lives but also the additional suffering of families and surrounding communities. The coordination between the studies on suicidal behavior and its complex network of individual and sociocultural factors and the studies on this multisystem autoimmune disease with a wide manifestation spectrum, which is lupus, creates a new and important field of research. Conclusion: non-psychiatrist office-based physicians, health clinics, or wards dedicated to the treatment of SLE should be able to recognize and handle the suicide risk factors on their patients in order to reduce the suffering caused by this disease.